HUBUNGAN PEMBERIAN POSTER TERHADAP KEPATUHAN MINUM OBAT PADA PASIEN DIABETES MELITUS DI PUSKESMAS SIMPANG EMPAT 1 KABUPATEN BANJAR - Muhammad Reza Pahlevi; Ratna Restapaty; Muhammad Alfayid (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2021)
The purpose of this study was to find out the compliance of patients take diabetes mellitus medicine by gave posters at Simpang Empat 1 public health center district Banjar. This study used a quasi-experimental method with cross sectional approach and prospective patient data collection. The samples diabetes mellitus patients treated at Simpang Empat 1 Health Center district Banjarin, namely as many as 338 patients. The results of this study showed that the group that was given a poster showed high results of compliance, with percentage 70.6%, in the group that was not given a poster resulted in low compliance as many as with percentage 41.2%. The results of the Mann-Whitney analysis p-value = 0.039 (<? = 0.05). The relationship between poster administration and medication compliance was shown by the Chi-Square analysis p-value = 0.037 (<?= 0.05). Base on this analysis, there are difference in drug compliance in the group give the poster with the group that is not give the poster. It can be conclud that there are a correlation between medication compliance in diabetes mellitus patients at the Simpang Empat 1 Public Health Center, District Banjar.